The Meaning of Fear of Failure for Final Year Students: A Phenomenological Approach Makna Fear Of Failure bagi Mahasiswa Tingkat Akhir : Sebuah Pendekatan Fenomenologi - Azimatus Zahro; Rani Amelia (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to explore the meaning of fear of failure among final-year students working on their undergraduate theses. Using a qualitative phenomenological approach, this research focuses on the subjective experiences of six informants selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and analyzed using Interpretative Phenomenological Analysis (IPA). The results show that fear of failure is interpreted as anxiety, fear, and emotional pressure triggered by internal and external expectations, including those from family, lecturers, and peers. Students experience procrastination, decreased motivation, and psychological distress; however, some perceive it as motivation for self-improvement. Strategies used by informants include communication with thesis advisors, time management, and seeking social support. These findings offer valuable insights for educational institutions in developing academic guidance strategies that also support students' mental well-being.